2010
DOI: 10.1111/j.1399-3046.2010.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adult‐sized kidneys in low‐weight pediatric recipients achieves short‐term outcomes comparable to size‐matched grafts

Abstract: Goldsmith PJ, Asthana S, Fitzpatrick M, Finlay E, Attia MS, Menon KV, Pollard SG, Ridgway DM, Ahmad N. Transplantation of adult‐sized kidneys in low‐weight pediatric recipients achieves short‐term outcomes comparable to size‐matched grafts.
Pediatr Transplantation 2010: 14:919–924. © 2010 John Wiley & Sons A/S. Abstract:  Low‐weight pediatric recipients are disadvantaged by scarcity of size‐matched donors. ASK have been successfully used for pediatric recipients. We report the results of renal transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Higher resistive indices are seen in children transplanted with an adult kidney which could increase the thrombotic risk or external vascular compression . However, our study is more consistent with recent reports, which did not show any increased risk for surgical‐related complications in pediatric renal transplants even with RAV/rBSA ratio mismatch . Furthermore, some authors have suggested that recent improvements in surgical technique may have prevented related morbidities such as graft loss or vascular complications in pediatric transplantation, especially the allograft placement in small abdominal space or even on the site of anastomosis …”
Section: Discussionsupporting
confidence: 90%
“…Higher resistive indices are seen in children transplanted with an adult kidney which could increase the thrombotic risk or external vascular compression . However, our study is more consistent with recent reports, which did not show any increased risk for surgical‐related complications in pediatric renal transplants even with RAV/rBSA ratio mismatch . Furthermore, some authors have suggested that recent improvements in surgical technique may have prevented related morbidities such as graft loss or vascular complications in pediatric transplantation, especially the allograft placement in small abdominal space or even on the site of anastomosis …”
Section: Discussionsupporting
confidence: 90%
“…Goldsmith et al [6] described how the scarcity of small paediatric donors required to size match donor and recipient would lead to unacceptably long waiting lists. They conducted a retrospective study between 1999 and 2008 of all paediatric renal transplants performed in their centre in Leeds, UK.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to children, there are further complications to consider in renal transplantation, ranging from the limited number of potential age-matched donors in developed countries to the relative lack of space in the young paediatric abdominal cavity to accommodate an extra solid organ [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Historically children under the age of 2 have had the highest posttransplant mortality; this statistic, however, has shown recent improvement (Goldsmith et al 2010). In the OPTN/SRTR annual data report for 2012 only 3 of the 2,262 children who received a kidney transplant from 2010 to 2012 were below 1 year of age (OPTN/SRTR 2012).…”
Section: Age and Sizementioning
confidence: 99%